Visual acuity after intravitreal ranibizumab with and without laser therapy in the treatment of macular edema due to branch retinal vein occlusion: a 12-month retrospective analysis - Reiko Umeya; Koichi Ono; Toshimitsu Kasuga (International Journal of Ophthalmology, 2021)
AIM: To identify factors contributing to visual improvement after treatment of macular edema (ME) secondary to branch retinal vein occlusion (BRVO), and to assess the interaction between laser therapy and intravitreal ranibizumab (IVR). METHODS: We retrospectively reviewed the medical records of patients who had been treated for BRVO-related ME at our hospital. Records were traceable for at least 12mo, and evaluated factors included age, sex, medical history, smoking history, treatment methods, foveal hemorrhage, and change in visual acuity. Treatments included laser therapy, IVR, sub-Tenon's capsule injection of triamcinolone (STTA), a combination, or no intervention. Multivariate logistic regression analysis and interaction terms were used to assess the clinical efficacy of the treatments, and odds ratios (OR) and 95% confidence intervals (CI) were calculated. RESULTS: Seventy-three patients (34 men, 39 women; 73 eyes) with a mean age of 69.4±12.1y were included. Patients who underwent IVR monotherapy, laser monotherapy, and STTA+laser had significantly higher best corrected visual acuity at 12mo compared to baseline (P<0.001, <0.001, and 0.019, respectively). Logistic regression analysis without interaction terms found that IVR was a significant visual acuity recovery factor (adjusted OR: 3.89, 95%CI: 1.25-12.1, P=0.019). Adjusted OR using an interaction model by logistic regression was 16.6 (95%CI: 2.54-108.47, P=0.003) with IVR treatment, and 8.25 (95%CI: 1.34-50.57, P=0.023) with laser treatment. No interaction was observed (adjusted OR: 0.07, 95%CI: 0.01-0.75, P=0.029). CONCLUSION: IVR contributes to improvements in visual acuity at 12mo in ME secondary to BRVO. No interaction is observed between laser therapy and IVR treatments.